Characteristics of a catalyst based on CoFe2O4 synthesis in a solar furnace - Muxammad S. Payzullahanov; Javohir Z. Shermatov; Otabek T. Rajamatov; Valentina G. Minkina; Sirojiddin SH. Makhmudov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: the synthesis method plays an important role in obtaining a material with a given particle size, structure, microstructure and specific surface area, and phase stability. These parameters together determine certain properties. The main synthesis methods are solid phase reactions, thermal decomposition, hydrothermal and solvothermal methods, co-precipitation, sol-gel and microwave processing. However, each method has its own advantages and disadvantages, and there is no optimal way to obtain high-quality ferrite materials from spinel. Therefore, the study of the structure and properties of cobalt ferrite CoFe2O4, synthesized from a melt of a mixture of Fe2O3 + CoO in a solar furnace is very interest. Aim: the obtaining a single-phase material representing a cubic modification of cobalt ferrite CoFe2O4 with a lattice parameter of 8.87 Å. The freshly synthesized material should exhibit a soft magnetic character with parameters Hc=60 Oe, Ms=30 emu/g; while the material fired at 1100°C exhibits increased parameters Hc=80 Oe, Ms=50 emu/g. Methods: the mixture was ground in an agate mortar with the addition of ethyl alcohol (10 wt.%) and molded into tablets with a diameter of 12 mm and a height of 15 mm. The tablets were placed on a melting table located on the focal spot of a circle shaped with a diameter of 30 mm of the solar furnace. The melt was cooled by pouring into water. Hardened castings were ground, molded, and sintered at 1100 oC. Results: the material obtained by synthesis from a melt in a solar furnace can be used in catalytic processes of hydrogen synthesis by reforming organic raw materials due to its structure and magnetic parameters.